Ovarian Pregnancy - Widayat Widayat; Ariadi Ariadi (Universitas Andalas, 2019)
Objective: To report cases of ovarian pregnancyMaterials and Methods: This article describes a case report of a 33 year old woman, with a diagnosis of Ovarian Pregnancy at 6-7 weeks gravid G2P0A1H0. The patient came to the emergency room Dr. M. Djamil Padang. The ultrasound examination gives the impression of an ectopic pregnancy in the right ampulla tube. After laparoscopy, an ectopic pregnancy was seen in the right ovary without bleeding. Right ovarian pregnancy impression. Partial Oophorectomy was performed and tissue evacuation with bleeding during the procedure ± 30 cc.Results: Patients receiving laparoscopic intervention showed an ectopic pregnancy in the right ovary without bleeding, the left ovary was within normal limits. Right ovarian pregnancy impression. Partial Oophorectomy was performed and tissue evacuation with bleeding during the procedure ± 30 cc. The tissue was examined for histology of anatomic pathology.Conclusion: Ovarian pregnancy is one of the rarest forms of ectopic pregnancy, it is sometimes difficult to diagnose because it can be confused with tubal ectopic pregnancy or hemorrhagic ovarian cyst. Pregnancy ovaries can rupture in the first trimester of pregnancy.Keywords: Ovarian Pregnancy, Laparoscopy, Partial Oophorectomy